2021
DOI: 10.3390/ijerph18147215
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, Socioeconomic Status, Social Distancing, Psychosocial Factors and Psychological Well-Being among Undergraduate Students during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic impacted on academic routine because of the social distancing measures. This study examined the relationships of sociodemographic characteristics, social distancing aspects and psychosocial factors on psychosocial well-being among undergraduate students during the social distancing period due to COVID-19. A web-based survey was conducted of undergraduate students at a public university in Brazil (n = 620). Demographics, socioeconomic status (SES), social distancing factors, negative affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
6
29
0
1
Order By: Relevance
“…The validation study of the social support scale in Brazilian adults reported a Cronbach’s alpha coefficient of at least 0.83 across the scale dimensions (Griep, Chor, Faerstein, Werneck, & Lopes, 2005 ). Previous research using the social support scale among Brazilian university students showed excellent internal consistency in all domains: material ( α = 0.85), affective ( α = 0.88), emotional ( α = 0.92), positive social interaction ( α = 0.94), and information ( α = 0.92) (Silva et al, 2021 ).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The validation study of the social support scale in Brazilian adults reported a Cronbach’s alpha coefficient of at least 0.83 across the scale dimensions (Griep, Chor, Faerstein, Werneck, & Lopes, 2005 ). Previous research using the social support scale among Brazilian university students showed excellent internal consistency in all domains: material ( α = 0.85), affective ( α = 0.88), emotional ( α = 0.92), positive social interaction ( α = 0.94), and information ( α = 0.92) (Silva et al, 2021 ).…”
Section: Methodsmentioning
confidence: 87%
“…Previous studies showed that SOC-13 presented satisfactory internal consistency when used among Brazilian adults ( α = 0.80) (Davoglio et al, 2016 ) and adolescents ( α = 0.67) (Silva et al, 2020 ). Cronbach’s alpha coefficient of the SOC-13 was 0.94 among undergraduate dental students in Brazil (Silva et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies conducted have highlighted the psychological effects and implications of this pandemic on the general population, such as anxiety, the fear or how demographics and socioeconomic status conditions can interfere with the psychological health of students during the interruption of the face-to-face teaching activities [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in this region of the world higher mental problem symptoms have been reported in the general population during the pandemic ( 19 ), and also before the pandemic for various reasons such as treatment gap ( 20 ). We have found three studies conducted in Brazil ( 21 23 ), two studies conducted in Mexico ( 24 , 25 ), and one in Chile ( 26 ). The studies in Brazil found that undergraduate students exhibited higher scores for perceived stress and depressive signs and lower resilience scores when compared to administrative and faculty staff ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies in Brazil found that undergraduate students exhibited higher scores for perceived stress and depressive signs and lower resilience scores when compared to administrative and faculty staff ( 21 ). Additionally, variables associated with symptoms of depression, anxiety and stress in Brazil were: being female, having a chronic disease, fewer positive relations with others, lower self-acceptance, self-blaming, and substance use ( 22 , 23 ). The studies in Mexico found that anxiety and depressive symptoms were related to younger age, previously diagnosed psychiatric disorder, and using drugs ( 25 ); and the main reason undergraduate students requested professional help was the presence of anxiety symptoms ( 24 ).…”
Section: Introductionmentioning
confidence: 99%